2019
DOI: 10.1002/sono.12177
|View full text |Cite
|
Sign up to set email alerts
|

The limitations of access to continuing professional development amongst Australia's rural sonographers and its effect on job satisfaction: A pilot study

Abstract: Introduction: Sonographers in Australia form an important component of health care within rural and remote communities. Being remotely located brings its own set of difficulties in accessing continuing professional development (CPD). There is little research investigating the rural sonographers' experience with access to CPD and how this affects job satisfaction. Method: The purpose of this research was to investigate if limited access to CPD is experienced in the rural setting, what barriers to participation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…The literature regarding positive and negative experiences where organisational or managerial support has affected practitioner engagement in CPD aligns with the findings of this study (6,13,16,18). The experience of the paramedic who dropped out of a tertiary degree is also echoed in health research that found participants reported an inability to engage in CPD, correlated to lack of job satisfaction, professional isolation and a decrease of confidence in clinical skills (22). There are jurisdictional ambulance service employers with polices, incentives and/or programs that support self-directed CPD (1).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The literature regarding positive and negative experiences where organisational or managerial support has affected practitioner engagement in CPD aligns with the findings of this study (6,13,16,18). The experience of the paramedic who dropped out of a tertiary degree is also echoed in health research that found participants reported an inability to engage in CPD, correlated to lack of job satisfaction, professional isolation and a decrease of confidence in clinical skills (22). There are jurisdictional ambulance service employers with polices, incentives and/or programs that support self-directed CPD (1).…”
Section: Discussionsupporting
confidence: 82%
“…A common finding in the literature, confirmed by this study, is the provision of gold standard care as an important factor associated with good CPD (3,4,6,11,14,18). The extant literature also describes time as one of the most commonly reported barriers to professionals engaging in CPD (3)(4)(5)(6)(8)(9)(10)(11)(12)(13)(17)(18)(19)(20)(21)(22). Paramedics are shift-workers who experience fatigue from workload and staffing shortages in some metropolitan and rural areas (1), therefore it was not surprising that the responses from the participants in this study mirrored those of other health professionals.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…There is a shortage of trained sonographers, especially in developing countries [50] - [51]. This situation warrants a tremendous demand for an automated fetal biometry system.…”
Section: A Problem Statementmentioning
confidence: 99%
“…professionally due to isolation, limited peer support and the lack of inter-professional team work. 6,7 There is a limited understanding of food security amongst initiative providers, particularly in how to enhance specific program areas; thinking outside of the normal scope and how their initiative functions as part of a larger system. 3 Food security policy makers often rely on systematic reviews to gain knowledge and evidence when implementing new strategies, however, this approach does not consider a local context.…”
mentioning
confidence: 99%